Recommended Bibliographic Information on the Sites of Children Libraries and Criteria for Assessing its Quality - N. A. Laut (Библиосфера, 2022)
As part of the implementation of the “Strategy for the Development of the Information Society in the Russian Federation for 2017–2030”, an important task is to develop criteria for assessing the social effectiveness of electronic services in the field of culture– in particular, in librarianship. When organizing children’s reading, the leading role is played by information and recommendation support, which can increase the interest of children-readers in books and create conditions for a safe information media environment. The purpose of the study is to analyze the qualitative characteristics of the provision of recommendatory bibliographic information on the websites of children libraries. The evaluation of the quality of websites is based on universal criteria for optimal provision of elements necessary for informing readers. They are: the quality of content and its relevance, visual design of the site and providing feedback to users. The evaluation is supplemented by two unique criteria: “ensuring the information and psychological safety of children” and “communicative and speech qualities of the texts of book annotations”. The use of such a system in the analysis of online library services on the example of the Russian State Children’s Library and six regional and municipal children libraries has shown that, in general, information and advisory support in the field of children reading management successfully fulfills the task of forming a virtual library space. The main drawbacks of some websites identified are the risks associated with advertising banners and links to third-party resources containing information with the age limit “18+”